1997
DOI: 10.1292/jvms.59.739
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of T-Cell Subsets in the Lymph Nodes from Cats Infected with Feline Immunodeficiency Virus

Abstract: ABSTRACT. Alterations of T-cell subsets in the lymph nodes from FIV-infected cats in various clinical disease stages were examined histologically. In the early stage of infection (AP stage), follicular hyperplasia accompanied by expansion of the paracortical area was observed. Follicular involution and depletion with reduced paracortical area was observed in the ARC and AIDS stage nodes. The maximum section area of the entire popliteal lymph node was expanded significantly in the AP nodes. The paracortical are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…The predominant B cell subset was IgM in all tissues. In lymph nodes, T cells were more abundant in the paracortex and the average CD4:CD8 ratios of lymph node T cells were similar to the ratios reported in other eutherian mammals (Black et al, ; Endo et al, ). When we compared the CD4:CD8 ratios of DFTD‐affected and nondiseased animals, there was no significant difference in the medulla or paracortex of the lymph node.…”
Section: Discussionsupporting
confidence: 83%
“…The predominant B cell subset was IgM in all tissues. In lymph nodes, T cells were more abundant in the paracortex and the average CD4:CD8 ratios of lymph node T cells were similar to the ratios reported in other eutherian mammals (Black et al, ; Endo et al, ). When we compared the CD4:CD8 ratios of DFTD‐affected and nondiseased animals, there was no significant difference in the medulla or paracortex of the lymph node.…”
Section: Discussionsupporting
confidence: 83%
“…Lymph node tissue has been examined most frequently, and reports consistently indicate nodal CD4+ depletion occurs as the disease progresses. [11,33,34] This study expanded on previous reports by reporting morphologic and immunohistochemical changes in spleen and intestines as well as lymph node tissue of the FIV-progressor cats. Interestingly, some of the differences identified through immunohistochemistry were not overtly evident in hematoxylin and eosin (H&E) stained sections.…”
Section: Discussionsupporting
confidence: 52%
“…43,44 In cats in the ARC and AIDS stages, histologic examination revealed the involution or depletion of lymph nodes. 12-14 Endo et al 15 identified that a decrease in CD4 + and CD8 + ymphocytes in lymph nodes was associated with disease progression to AIDS. Although lymphocyte depletion has been detected in cats in advanced clinical stages of FIV infection, 12,14 there was not a significant correlation between total lymphocyte count and clinical stage of disease (Student t-test) or plasma viral RNA concentration (Spearman rank-order correlation).…”
Section: Discussionmentioning
confidence: 99%